Predicting preschool children's emotional eating: The role of parents' emotional eating, feeding practices and child temperament. Issue 3 (27th February 2022) - Stone, Rebecca A.; Blissett, Jacqueline; Haycraft, Emma; Farrow, Claire
Abstract: Emotional eating (EE; defined as overeating irrespective of satiety and in response to emotional states) develops within childhood, persists into adulthood, and is linked with obesity. The origins of EE remain unclear, but parental behaviours (e.g., controlling feeding practices and modelling) and child characteristics (e.g., temperament) are often implicated. To date, the interaction between these influences has not been well investigated. This study explores whether the relationship between parent and child EE is shaped by parental feeding practices, and if the magnitude of this relationship varies as a function of child temperament. Mothers ( N = 244) of 3–5‐year‐olds completed questionnaires about their EE, feeding practices, their children's EE and temperament. Results showed that parental use of food to regulate children's emotions fully mediated the relationship between parent and child EE, and using food as a reward and restricting food for health reasons partially mediated this relationship. Analyses demonstrated that the mediated relationship between parent and child EE via use of food as a reward and restriction of food for health reasons varied as a function of child negative affect, where high child negative affect moderated these mediations. These findings suggest child EE may result from interrelationships between greater parent EE, use of food as a reward, restriction of food for health reasons and negative affective temperaments, but that greater use of food for emotion regulation may predict greater child EE irrespective of child temperament. Key messages: Child temperament moderates the significant mediating relationships between parent EE, certain parental feeding practices and child EE. Parental use of food as a reward significantly mediates the relationship between parent and child EE only for children who are medium or high in negative affect. Parental restriction of food for health reasons significantly mediates the relationship between parent and child EE only for children who are high in negative affect. In children who are low in negative affect, parental rewarding and restrictive feeding practices do not mediate the relationships between parent and child EE. Models of eating behaviour should consider how child characteristics can shape the expression and influence of behaviours that are known to place children at greater risk of obesogenic eating behaviours. Abstract : Parental feeding practices have previously been shown to mediate the relationship between parent and child emotional eating. In this study, we find that this mediating relationship is only significant for children with certain temperament dispositions; specifically, parental use of food as a reward and restriction of food for health reasons mediate the relationships between parent and child emotional eating, but only for children with medium to high negative affect. The contribution of child temperament should be considered alongside that of parenting when exploring the development of emotional eating in children.